Recovery identity as a buffer: mitigating trauma's impact on recovery capital in collegiate recovery programs - Francis, Meredith; Smith, Rebecca; Miola, Rose; Yang, Ya-Li; Bannard, Thomas; Burns, Victoria; Cleveland, Michael; Karimova, Konul; LaBelle, Onawa; Murphy, Declan; Piccirillo, Marilyn (Frontiers in Adolescent Medicine, 2025)
IntroductionExperiencing trauma is well-known to negatively impact AOSUD recovery and recovery capital. However, having a stronger recovery identity positively impacts recovery capital, and can be strengthened through recovery-supportive relationships. Identity change and reconstruction is also central to trauma healing, making it likely that recovery identity buffers the effect of trauma on recovery capital. This study examines this relationship and identifies types of recovery supports that facilitate development of stronger recovery identity within participants in collegiate recovery programs (CRPs).MethodsThe sample consisted of participants in the National Longitudinal Collegiate Recovery Study who completed all measures at their baseline assessment (N = 168). Total scores of the PCL-5 short form (trauma) and Recovery Identity scale (RI) were regressed on the Brief Assessment of Recovery Capital (BARC) total score. Measures of recovery support, including a measure of support from CRP staff and individual yes/no questions about experiencing various recovery supports, were regressed on RI scores.ResultsLower PCL-5 scores and higher RI scores both significantly predicted higher recovery capital scores [adjR2 = .51; F(3, 168) = 59.61, p < .001], and interacted such that having higher RI scores buffered the impact of having higher trauma scores on recovery capital [ΔR2 = .01, F(4, 168) = 46.66, p < .001]. Perceiving CRP staff (β = .04, p = .007) and peers in recovery (β = .32, p < .001) as being supportive of one's recovery significantly predicted higher recovery identity scores [adjR2 = .16; F(5, 173) = 107.01, p < .001].ConclusionHaving a stronger recovery identity buffers the impact of trauma symptoms on recovery capital for CRP participants. CRP participants who perceive their CRP staff as being strong role models and providing a safe, welcoming recovery space and who have support from peers in recovery had stronger recovery identities. CRPs can help participants with higher trauma levels to build recovery-supportive relationships with their peers, and can create supportive, trauma-responsive spaces for all participants.